2014
DOI: 10.1586/17469899.2014.951331
|View full text |Cite
|
Sign up to set email alerts
|

Update on the prevention and treatment of endophthalmitis

Abstract: SUMMARY Endophthalmitis remains a rare but serious cause of visual loss. Over time, changes have been noted in endophthalmitis in terms of predominant causes, infecting organisms, and antibiotic susceptibilities. There is controversy regarding the use of intracameral prophylactic antimicrobials during cataract surgery. Alternatively, there appears to be increasing evidence against using routine topical antibiotics for intravitreal injections. There are also increasing reports of multidrug-resistant organisms c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Other methods to increase the concentration of antibiotic in the anterior chamber include improved formulations of topical agents and bottles (such as medication concentration, pH and instillation volume) that could improve corneal penetration, particularly with regard to aminoglycosides . Intraocular lenses soaked in antibiotics and antibiotic nanoparticles may also hold a future role in endophthalmitis prevention …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Other methods to increase the concentration of antibiotic in the anterior chamber include improved formulations of topical agents and bottles (such as medication concentration, pH and instillation volume) that could improve corneal penetration, particularly with regard to aminoglycosides . Intraocular lenses soaked in antibiotics and antibiotic nanoparticles may also hold a future role in endophthalmitis prevention …”
Section: Discussionmentioning
confidence: 89%
“…41 Intraocular lenses soaked in antibiotics and antibiotic nanoparticles may also hold a future role in endophthalmitis prevention. 42,43 Although this study accessed endophthalmitis cases from a large population, 18% of the cases were not cultured. This is a consequence of the study being set in a community-based population.…”
Section: Discussionmentioning
confidence: 99%
“…It is more frequently used as a first election treatment in this pathology, in monotherapy or combined with other antibiotics, since it allows reaching ocular concentrations in the order of 35.4 mg/l after intravenous administration of a 100 mg/kg antibiotic dose [161]. Intravenous [165][166][167] In addition to these, different intravenous drug delivery strategies have been tested for drug arrival to the posterior segment of the eye [168]. Specifically, photodynamic therapy with verteporfin has been practiced, being a choroidal neovascularization effective treatment by stopping the neovascular membrane growth.…”
Section: Systemic Drugs For Posterior Segment Eye Diseasesmentioning
confidence: 99%
“…In fact, large studies have shown that topical antibiotics may even increase the rate of EO. It was hypothesized that the repeated antibiotic exposure, promoting the development of resistant strains, may lead to this paradox finding [103, 104]. Thus, there is no evidence to consider perioperative antibiotics as a standard of care [104-106].…”
Section: Peri- /Injection Management In Intravitreal Pharmacotherapymentioning
confidence: 99%